Reinventing Community Corrections - Cullen, Francis T. (Crime and justice, 2017)
Community corrections in the twenty-first century faces three challenges: how to be an alternative to imprisonment, how to be a conduit for reducing recidivism, and how to do less harm to offenders and their families and communities. Community corrections will reduce imprisonment only if its use is viewed as a legitimate form of punishment and is incentivized, which involves subsidizing the use of community sanctions and making communities pay to imprison offenders (e.g., a cap-and-trade system). To reduce recidivism, it will be necessary to hold officials accountable for this outcome, to ensure that evidence-based supervision is practiced, to use technology to deliver treatment services, and to create information systems that can guide the development, monitoring, and evaluation of interventions. Doing less harm—avoiding iatrogenic effects—will require nonintervention with low-risk offenders, reducing the imposition of needless constraints on offenders (i.e., collateral consequences), and creating opportunities for offenders to be redeemed.